Pemikiran Pendidikan Islam Menurut K.H. Hasyim Asy’ari - Dhevin M.Q Agus Puspita W (FALASIFA : Jurnal Studi Keislaman, 2019)
KH Hasyim Asy'ari is a scholar who was born from an elite family of kiai in the Jombang area, he had studied at various boarding schools in Java before continuing his education to the Hijaz land. Then he returned to Indonesia and established the Tebuireng Jombang boarding school which is famous for its hadith science. The depth of knowledge, and his thinking in education is very brilliant, so he got the title "Hadratus Shaykh" which means "Mr. Professor". Hasyim Asy'ari's thoughts in the field of Education are more viewed in terms of ethics in education. which relates to the principles of the implementation of education and psychology in the world of education which then gave birth to an effective personality for students and teaching. One of Hasyim Asy'ari's monumental works is the book entitled Adab al Alim wa al Muta'allim fima Yahtaj ilah al Muta'alim fi Ahuwal Ta'allum wama Yataqaff al Mu'allim fi Maqamat Ta'limih, In that book he summarizes his thoughts about Islamic education into eight points, namely: a) The virtue of knowledge and the importance of teaching and learning. b) Ethics that must be considered in teaching and learning, c) Ethics of a student to the teacher, d) Ethics of a student regarding lessons and things that must be guided by the teacher, e) Ethics that must be guided by a teacher, f) Ethics of the teacher when and will teach, g) The ethics of the teacher towards his students, h) The ethics of books, tools for getting lessons and things related to it. Furthermore, in the eight theories about education are summarized in thethree concepts first, the significance of education. second, the tasks and responsibilities of students. Third, the duties and responsibilities of the teacher.